2022
DOI: 10.3389/feart.2022.886512
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Biases Associated With Dietary Starch Incorporation and Retention With an Oral Biofilm Model

Abstract: Dental calculus has proven to contain a wealth of information on the dietary habits of past populations. These insights have, to a large extent, been obtained by the extraction and identification of starch granules contained within the mineralised dental plaque from a wide range of regions and time periods. The scope of previous studies have been limited to microfossil extraction and identification to reconstruct dietary preferences from the archaeological record, and few studies have attempted to address the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…However, there is increasing recognition of the interpretive constraints that limit the utility of these analyses as a proxy for past diet [84][85][86]. Studies continue to highlight the variability of recovered microparticle assemblages that present a partial record of dietary intake and fail to capture dietary breadth at the individual level [87,88]. As such, dental calculus studies are increasingly applying larger population approaches embedded in multiproxy frameworks [57,58,[89][90][91][92].…”
Section: A Multiproxy Approach To Reconstructing Past Dietmentioning
confidence: 99%
“…However, there is increasing recognition of the interpretive constraints that limit the utility of these analyses as a proxy for past diet [84][85][86]. Studies continue to highlight the variability of recovered microparticle assemblages that present a partial record of dietary intake and fail to capture dietary breadth at the individual level [87,88]. As such, dental calculus studies are increasingly applying larger population approaches embedded in multiproxy frameworks [57,58,[89][90][91][92].…”
Section: A Multiproxy Approach To Reconstructing Past Dietmentioning
confidence: 99%
“…Raw potato and wheat starch solutions were added during the biofilm growth to explore the biases involved in their incorporation and extraction from dental calculus. These results are presented in a separate article (Bartholdy & Henry, 2022).…”
Section: Methodsmentioning
confidence: 92%
“…An 𝛼-amylase assay conducted on samples from days 3, 6, 8, 9, 10, 12, and 14 also showed that there was no host salivary 𝛼-amylase activity in the system. The results of the starch incorporation and 𝛼-amylase activity assay have been reported in a separate article (Bartholdy & Henry, 2022).…”
Section: Biofilm Growthmentioning
confidence: 98%
See 1 more Smart Citation